Frontiers of environmental economics - Folmer, Henk, 1945-; Edward Elgar Publishing (Cheltenham, U.K. ; Northampton, Mass. : Edward Elgar, 2001)
Top European and American scholars contribute to this cutting-edge volume on little-researched areas of environmental and resource economics. Topics include spatial economics, poverty and development, experimental economics, large-scale risk and its management, organizational economics, technological innovation and diffusion and many more.
1. Green accounting and green taxes in the global economy -- 2. The environment and economic well-being -- 3. Spatial economic aspects of the environment and environmental policy -- 4. Empowering the community : information strategies for pollution control -- 5. To whisper in the ears of princes : laboratory economic experiments and environmental policy -- 6. The firm, its procedures and win-win environmental regulations -- 7. International trade and the environment : how to handle carbon leakage -- 8. Poverty, environment and development -- 9. Industrial ecology : wealth, depreciation and waste -- 10. Ecosystems as lotteries -- 11. Corporate governance in the presence of major technological risks -- 12. Strategies for dealing with large-scale natural and environmental risks -- 13. Resilience and sustainability -- 14. Environmental technological innovation and diffusion -- 15. On the future of environmental economics.
Referred to selection officer for imperfect copy decision.
Includes bibliographical references and index.
Keywords: Environmental economics; Natural resources; Electronic books